Is playing soccer more osteogenic for females before the pubertal spurt? - Lozano-Berges, G.; Matute-Llorente, A.; Gómez-Bruton, A.; González-Agüero, A.; Vicente-Rodriguez, G.; Casajús, J. A. (Journal of Human Kinetics, 2019)
The aims of this study were to assess bone mass in children and adolescent soccer players and to evaluate the influence of both gender and pubertal status on bone mass. A total of 110 soccer players (75 males / 35 females; 12.73 ± 0.65 / 12.76 ± 0.59 years) participated in this cross-sectional study. They were divided into two groups according to their pubertal status. Bone and lean masses were measured with Dual-energy X-ray Absorptiometry. An independent t-test and an adjusted by subtotal lean and training experience multivariate analysis of covariance were used to analyse the differences in bone mass values between genders and maturity status. Female soccer players presented higher bone mass values than their male counterparts in most of the measured weight-bearing sites. Moreover, when stratifying by pubertal status, peripubertal and postpubertal females had higher subtotal body and lumbar spine bone mass than males. Comparing between pubertal status groups before adjustment, both male and female postpubertal players showed higher bone mass than their pubertal counterparts. After adjusting, these differences disappeared and, in fact results were inverted as bone mass at the femoral neck was higher in both male and female peripubertal soccer players than in postpubertal players. Bone mass seems to be more intensely stimulated by playing soccer in female than male players, particularly in the lumbar spine. The results of peripubertal players showing higher bone mass at the femoral neck after adjusting suggest that playing soccer during the peripubertal stage could be an effective activity to achieve optimal bone mass values. Keywords: soccer; sports; bone density; adolescent